PENGARUH LATIHAN OTOT TUNGKAI TERHADAP KETERAMPILAN TENDANGAN T PADA ATLET PENCAK SILAT UPI KAMPUS SUMEDANG - Oktova, Fikri Dwi; Muhtar, Tatang; Alif, Muhammad Nur (Fakultas Ilmu Keolahragaan Unimed, 2024)
This study aims to determine leg muscle training in performing T kicks on UPI martial arts athletes, Sumedang Campus. Because in doing T kicks, there are still many athletes who lack leg muscle training so that they are not precise when doing T kicks. And at this time researchers want to know how influential leg muscle training is on the accuracy of T kicks in UPI martial arts athletes, Sumedang Campus. Researchers took samples of 10 UPI Sum Campus pencak silat athletes. This study used quantitative types with experimental methods with One-Group Pretest posttest design. This researcher data collection uses observation, literature techniques, tests or measurements and also statistical applications to obtain final results